The Characteristics of the Listed Companies Violated the Securities and Exchange Act B.E. 2535 and Impact on Stock Prices - พรมทอง, ภัณฑิลา; ปวีณพงษ์พัฒน์, ศิลป์ชัย (KKBS Journal of Business Administration and Accountancy, 2017)
This study aimed at identifying characteristics of the listed companies violated The Securities and Exchange Act B.E. 2535 and the response of stock prices on the announcement of violation. The characteristics used for this study comprised of firm size, shareholder structure, corporate governance, and audit firm size. The samples for the study were companies listed on The Stock Exchange of Thailand (SET), as well as stock Market for Alternative Investment (MAI) which were on the announcement of violation by The Securities and Exchange Commission (SEC) during 2010 – 2015 for the numbers of 47 companies and 63 events. The method used here is t-Test and Chi-Square test at the level of confidence 95% The findings revealed that the violated companies had smaller firm size, less corporate governance and more audited by small audit firms (Non-Big 4) than the non-violated companies. Whereas, in regard to the shareholder structure, there wasno difference in the shareholders structure between violated companies and non-violated companies. Regarding the test results on the response of stock prices, there was negative impact on stock prices when announcement the violation. In addition, he violated companies with the criminal penalties had negative impact on stock prices more than the violated companies with the fine penalties on statistical significance.